Diagnosis and management of congenital thrombophilia in the era of direct oral anticoagulants. Issue 185 (January 2020) - Alameddine, R.; Nassabein, R.; Le Gal, G.; Sié, P.; Mullier, F.; Blais, N.
Abstract: Direct oral anticoagulants (DOAC)s are often preferred to other anticoagulants as they are more practical and do not require routine laboratory monitoring. Less is known about their use in congenital thrombophilia. Efficacy of DOACs in congenital thrombophilia, effect of DOACs and other anticoagulants on diagnostic tests as well as efficacy and safety of anticoagulant use in this population is still a matter of debate. In this review we intended to analyze the potential pitfalls of testing for thrombophilia in patients using DOACs and vitamin K antagonists (VKA)s as well as to suggest strategies to improve diagnostic accuracy in this setting. We also reviewed the literature for evidence regarding the safety and efficacy of DOACs in patients with congenital thrombophilia. Some evidence was found supporting the use of DOACs in low risk thrombophilia, although evidence for their use in high risk thrombophilia is limited to small series and case reports. Our findings support the generation of better evidence to support DOAC use for congenital thrombophilia, especially in the high risk subgroups. Highlights: Thrombophilia testing while on anticoagulants is often misleading and may lead to inappropriate diagnosis. Some evidence exists to support similar efficacy of DOACs and Vitamin K antagonists in the setting of low risk thrombophilia. Evidence supporting DOACs for high risk hereditary thrombophilia is limited to small case series. There are advantages and potential risks of DOACs in the setting of high risk thrombophilias . A personalized approach is suggested.